The Role of The United Nations Committee on the Peaceful Uses of Outer Space - I Nyoman Prabu Buana Rumiartha (Focus Journal : Law Review, 2022)
Based on the provisions of Article 1 Paragraphs 1 and 4 of the United Nations Charter, it is stated that the purpose of the United Nations is to maintain international peace and security, in this case to take effective collective action for the prevention and elimination of threats to peace, to suppress acts of aggression. or other violations, to bring it about by peaceful means and in accordance with the principles of justice and international law, adjustments or adjustments to the international situation that may lead to peace and the United Nations, as well as centers to harmonize the actions of nations in peace with common goals. So to realize these things, the United Nations establishes international bodies that regulate the regulations that apply when problems occur between countries in the world, furthermore for the regulation of the peaceful use of outer space in this case the United Nations, formed The United Nations Committee on the Peaceful Uses of Outer Space (UN-COPUOS) and the Division of Outer Space Affairs, as an important committee in overseeing the peaceful use of outer space. The United Nations General Assembly in Resolution 1348 (XIII) established an ad hoc Committee on the Peaceful Use of Outer Space. As well as the 1967 Treaty on the principles governing the activities of countries in the exploration and use of outer space, including the moon and other celestial bodies.